Genotoxic Mechanism of Action of TBBPA, TBBPS and Selected Bromophenols in Human Peripheral Blood Mononuclear Cells - Barańska, Anna; Woźniak, Agnieszka; Mokra, Katarzyna; Michałowicz, Jaromir (Frontiers in Immunology, 2022)
Bromophenolic flame retardants (BFRs) are a large group of synthetic substances used in the industry in order to reduce the flammability of synthetic materials used in electrical and electronic devices, textiles, furniture and other everyday products. The presence of BFRs has been documented in the environment, food, drinking water, inhaled dust and the human body. Due to the widespread exposure of the general population to BFRs and insufficient knowledge on their toxic action, including genotoxic potential, we have compared the effect of tetrabromobisphenol A (TBBPA), tetrabromobisphenol S (TBBPS), 2,4,6,-tribromophenol (2,4,6-TBP) and pentabromophenol (PBP) on DNA damage in human peripheral blood mononuclear cells (PBMCs) (playing a crucial role in the immune system) as well as examined underlying mechanism of action of these substances. The cells were incubated for 24 h with studied compounds in the concentration ranging from 0.01 to 10 µg/mL. The study have shown that examined BFRs induced single and, to a lesser extent, double strand-breaks formation and caused oxidative damage to pyrimidines, and particularly to purines in the incubated cells. PBMCs efficiently repaired the DNA strand-breaks induced by BFRs, but they were not able to remove completely damaged DNA (except cells treated with TBBPS). The greatest changes in the above-mentioned parameters were observed in cells incubated with TBBPA, while the smallest in PBMCs treated with TBBPS. The results also revealed that tested compounds did not form adducts with DNA in PBMCs, while the observed changes were the most probably induced by indirect DNA-damaging agents, such as ROS and other reactive species.